Cows and Humans as Technology Users: Multispecies Agency and Gender in Automated Milking Systems in Finland - Kaarlenkaski Taija (United States, 2025)
Automatization has changed the interaction between cows and humans in subtle ways. Automated milking systems (AMS) have been used commercially since the early 1990s, first in the Netherlands, then in Western Europe and North America, before reaching Finland. By 2021, nearly 27 percent of Finnish dairy farms have adopted them. Based on fieldwork at AMS farms and Finnish trade journal items, this article argues that as technology users, both humans and cows are engaged in agential entanglements with milking robots. It highlights challenges that cows and farmers face in learning to use the milking robot, how it impacts their working and living rhythms, and how the technologized work with AMSs is gendered among dairy farmers.